Comparison of Real and Revelative Working Areas in Islamic Law - Syarifuddin Syarifuddin (International Journal of Nusantara Islam, 2020)
One of the human potentials that is very valuable as well as distinguishes it from other creatures is reason. The messages of Allah, both expressed through the redaction of His revelation in the Koran and implied in His creation, can be revealed by reason, so that the purpose of law (Maqashid al-Sharia) contained in it can be known and manifested in life real. The use of reason in the area of legal work, let alone to determine or stipulate a law, became a long debate for Islamic thinkers after the Prophet Muhammad died. Even though they agree that the third source of Islamic law is reason (al-Ra'yu) but in their ijtihad the mujtahids use reason in different portions and methods. Some use it very large, and some are very small portions. In general, the jurisdiction can be distinguished in the form of at-Ta'abbud, namely the legal area which is the right of Allah (haqqullah) and at-Ta'aqqul, namely the legal area which is the right of Insan (haqqul Ibad / insan /) to think about it. In the latter area it is the authority of reason.